Anti-HIV activity in traditional Chinese medicine: clinical implications of monomeric herbal remedies and compound decoctions - Zhang, Nannan; Wang, Mengyuan; Gao, Ling; Zhang, Congying; Tang, Xiaoguang; Liu, Xianjun; Bai, Chunying (Frontiers in Medicine, 2024)
With the global spread of human immunodeficiency virus (HIV) infection and acquired immune deficiency syndrome (AIDS), the pursuit of potent treatments has ascended as a paramount concern in global healthcare. Traditional Chinese medicine (TCM) has been used for thousands of years in China and other East Asian countries and it offers remedies for an extensive array of ailments, including HIV and AIDS. This review focuses on the clinical significance of single herbs and composite tonics in TCM with antiviral activity against HIV. Initially, the anti-HIV activity of single herbs was analyzed in detail. Many herbs have been shown to have significant anti-HIV activity. The active ingredients of these herbs exhibit their anti-HIV effects through various mechanisms, such as inhibiting viral replication, preventing viral binding to host cells, and interfering with the viral lifecycle. Furthermore, we delved into the clinical significance of HIV-associated formulations provided as a result of Chinese compound prescription. These combinations of herbal ingredients are designed to amplify therapeutic efficacy and minimize adverse effects. Clinical trials have demonstrated the therapeutic benefits of these prescriptions for individuals infected with HIV. The intricate composition of these prescriptions potentially augments their anti-HIV activity through synergistic effects. Additionally, this review underscores the clinical importance of TCM in the context of HIV treatment. While numerous herbs and prescriptions exhibit anti-HIV activity, their safety and efficacy in clinical applications warrant further investigation. When combined with contemporary antiretroviral drugs, TCM may serve as an adjunctive therapy, assisting in reducing side effects, and enhancing patients' quality of life. To optimally harness these natural resources, further exploration is imperative to ascertain their efficacy, safety, and optimal utilization, thereby offering a broader spectrum of therapeutic options for HIV-afflicted individuals.